2021
DOI: 10.1021/acs.inorgchem.1c01118
|View full text |Cite
|
Sign up to set email alerts
|

Improving Room Temperature Ionic Conductivity of Na3–xKxZr2Si2PO12 Solid-Electrolytes: Effects of Potassium Substitution

Abstract: The battery safety and cost remain major challenges for developing nextgeneration rechargeable batteries. All-solid-state sodium (Na)-ion batteries are a promising option for low-cost as well as safe rechargeable batteries by using abundant resources and solid electrolytes. However, the operation of solid-state batteries is limited due to the low ionic conductivity of solid electrolytes. Therefore, it is essential to develop new compounds that feature a high ionic conductivity and chemical stability at room te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 38 publications
(68 reference statements)
2
2
0
Order By: Relevance
“…40 In another, experimental, study, it was shown that 10% substitution of larger K + for Na + in monoclinic NaSICON-type Na 3−x K x Zr 2 Si 2 PO 12 increases conductivity and decreases activation energy. 41 This is consistent with the strong response of the framework to the size mismatch between the A and the A site, discussed in Section 2.4 and illustrated in Figure 11c. Based on that, we can formulate at least two practical recommendations for optimizing NaSICON-type frameworks to increase ionic conductivity, as follows.…”
Section: A-ion Transport Bottlenecks and Free Volume Vs (M−o)/(t−o)supporting
confidence: 87%
See 1 more Smart Citation
“…40 In another, experimental, study, it was shown that 10% substitution of larger K + for Na + in monoclinic NaSICON-type Na 3−x K x Zr 2 Si 2 PO 12 increases conductivity and decreases activation energy. 41 This is consistent with the strong response of the framework to the size mismatch between the A and the A site, discussed in Section 2.4 and illustrated in Figure 11c. Based on that, we can formulate at least two practical recommendations for optimizing NaSICON-type frameworks to increase ionic conductivity, as follows.…”
Section: A-ion Transport Bottlenecks and Free Volume Vs (M−o)/(t−o)supporting
confidence: 87%
“…The increase of the [LiO 6 ] polyhedra volume in turn was shown to correlate with the reduced migration activation energy calculated by the Nudged Elastic Band method . In another, experimental, study, it was shown that 10% substitution of larger K + for Na + in monoclinic NaSICON-type Na 3– x K x Zr 2 Si 2 PO 12 increases conductivity and decreases activation energy . This is consistent with the strong response of the framework to the size mismatch between the A and the A site, discussed in Section and illustrated in Figure c.…”
Section: Discussionsupporting
confidence: 72%
“…Considering the sodium ion version, Na 1+x Zr 2 Si x P 3−x O 12 , the highest ionic conductivity obtained is for x = 2, Na 3 Zr 2 PSi 2 O 12 with an ionic conductivity of approximately 1.13 mS cm −1 at RT. 22 However, several doping strategies have been employed to achieve higher ionic conductivities: (1) doping with potassium ions, which demonstrated for Na 2.303 -K 0.099 Zr 2 Si 1.880 P 1.106 O 12 an ionic conductivity of 0.8 mS cm −1 at RT; 23 (2) doping with Ge, Na 3.125 Zr 1.75 Sc 0.125 Ge 0.125 Si 2 PO 12 , resulted in total ionic conductivity 4.6 mS cm −1 ; 24 (3) doping with Sc, Na 3.4 Zr 1.6 Sc 0.4 Si 2 PO 12 provides an RT ionic conductivity of 4.0 mS cm −1 . 22 As for perovskite electrolytes, one notable example is Li 3x La (2/3)−x TiO 3 LLTO.…”
Section: Features Enabling Energy Storagementioning
confidence: 99%
“…4,5 Therefore, designing solid-state electrolytes (SSEs) for NIBs has attracted tremendous research attention in recent years. 6–13 To date, SSEs for NIBs have been mostly based on oxides, sulfides and halides, 14,15 such as β-alumina, 16,17 NASICON, 18,19 Na 3 PS 4 (ref. 20) and Na 3 OCl.…”
Section: Introductionmentioning
confidence: 99%